The effect of monitoring 'processing style' on post‐surgical neuropathic pain in women with breast cancer. (8th December 2014) - Sherman, K.A.; Winch, C.J.; Koukoulis, A.; Koelmeyer, L.
Abstract: Background: Pain is a commonly reported symptom following surgery that is more likely to occur in individuals psychologically distressed prior to surgery. Monitoring processing style, a cognitive tendency to focus on health‐related threats, has been associated with increased reporting of somatic symptoms, but no studies have specifically addressed the link between this cognitive style and pain. This prospective clinical study aimed to investigate whether monitoring processing style predicted post‐surgical pain in women undergoing breast surgery, controlling for pre‐surgical psychological distress. Methods: Women scheduled to undergo breast cancer surgery ( N  = 106) completed pre‐surgical assessments of monitoring processing style (Miller Behavioral Style Scale) and psychological distress (Depression Anxiety Stress Scales‐21). Demographic and medical characteristics were documented. Self‐reported neuropathic pain (Neuropathic Pain Scale) was assessed at 3 months post surgery. Results: Post‐surgical neuropathic pain levels were low to moderate ( M  = 19.3, SD  = 21.1). Higher pre‐surgical monitoring processing style scores significantly predicted higher post‐surgical neuropathic pain (β  =  0.23, p  = 0.023), over and above psychological stress (β = 0.22, p  = 0.020) and age (β = −0.25, p  = 0.011). Conclusions: Pre‐surgical monitoring processing style was an independent predictor of post‐surgical neuropathic pain, even when accounting for pre‐surgical psychological distress. Since the reduction of post‐surgical pain is a key goal of healthcare, efforts should be made prior to breast cancer surgery to counsel and support individuals with high monitoring processing styles irrespective of their level of distress.